Indução de brotações epicórmicas ortotrópicas para a propagação vegetativa de árvores adultas de Araucaria angustifolia - Wendling, Ivar (Universidad de Costa Rica, 2009)
This study evaluated 4 epicormic (lateral sprouts) sprout-induction methods with adult ( > 20-year-old) araucaria trees: a) branch pruning up to 2/3 total height and leaving 3 different branch sizes in the stem (2-3 cm, 20 cm, and 50 cm); b) 50-cm long cuttings from branches with 30-60 mm diameter and placed in greenhouse or under shade; c) sprouts from stumps; and d) top pruning. It was observed that branches pruned at 20-50 cm long produced more sprouts. Cuttings 50 cm long under shade registered more sprouts than those placed in the greenhouse. Stumps produced 60% sprouts 5-37 cm long, varying from 7-59 single sprouts per stump. One year later, 50% of top-pruned trees produced enough sprouts ( > 5 cm long) to be harvested. It is concluded that branches pruned at 20 to 50 cm long, and basal stumps, were the most efficient sprout producers, especially with orthotropic growth. Meanwhile, long cuttings were not efficient due to high mortality and low sprout induction. Top pruning has a potential, especially for grafting purposes, but still showing low sprout production.